Application of electromagnetic continuous variable transmission in hydraulic turbines to increase stability of an off-grid power system. (August 2022) - Achitaev, Andrey A.; Suslov, Konstantin V.; Nazarychev, Alexander N.; Volkova, Irina O.; Kozhemyakin, Vyacheslav E.; Voloshin, Alexander A.; Minakov, Andrey V.
Abstract: In the context of climate change, today's adoption of renewable energy sources in isolated power systems is becoming an increasingly more significant issue. Micro-hydro power plants are emerging as a mature balancing technology and a great alternative to large hydropower plants as they do not encounter population displacement and many environmental problems. It is worth noting that hydroelectric power plants combined with various sources require improvement in control laws and algorithms. Strong disturbing impacts, namely transient processes, in an isolated electric power system cause an appreciable decrease in dynamic stability. This paper presents research conducted to ensure synchronous parallel operation of permanent-magnet generators used in micro-hydroelectric power plants in an isolated power system with a controllable flexible coupling between turbine and generator. The importance of this study lies in the issue of electromechanical compatibility to be achieved in parallel operation of generators that have different parameters of time constant of mechanical inertia of rotors of electrical machines. This paper provides an overview of possible solutions to the identified problem. A concept based on a controllable flexible coupling between generator and turbine is proposed as a promising avenue to solve this problem. The mathematical models are presented along with the laws and algorithms developed for automatic control of the generator speed. Oscillograms of simulation and physical modeling presented in the final part of the paper show parallel operation of permanent-magnet synchronous generators in an isolated electric power system for various electrical distances of three-phase short circuit points. Highlights: Increasing the dynamic stability of an isolated power system. Electromagnetic correction of turbine and generator. Electromechanical transients with controlled flexible coupling. Mathematical modeling of a hydraulic turbine.